PENGARUH PERSEPSI KEMUDAHAN DAN PERSEPSI KEAMANAN TERHADAP MINAT PENGGUNAAN E-MONEY DI KALANGAN GENERASI MILLENIAL - Adinda; Mardhiyah, Ainun (Talenta Publisher, 2022)
Technological advances in payment systems are slowly shifting the role of cash as a means of payment to more efficient and economical forms of non-cash payments. Therefore, the development of the use of non-cash payment instruments needs serious attention. This study aims to determine how the Effect of Perceptions of Ease and Perceptions of Security on Interest in Using E-money. This study uses quantitative research methods with an associative approach. The population in this study were e-money users in the Medan Baru District area. The results showed that the Ease of Perception had a positive and significant effect of 27.1% on Interest in Using E-money and Perception of Security had a positive and significant effect of 40% on Interest in Using. Based on calculations with the coefficient of determination, the R value is 81.9%, which indicates that the relationship between perceived convenience and perceived security on interest in using e-money is quite close. The Rsquare value of 0.671 indicates that 67.1% of the Usage Interest variable can be explained by the Ease of Perception and Perception of Security. While the rest is influenced by other variables not examined in this study.